Retrofit Strategies for Seismic Protection of Multi-Story Structures with Extended KDamper Devices - Kapasakalis, Konstantinos; Mantakas, Antonios; Kalderon, Moris; Sapountzakis, Evangelos (Technical Annals, 2024)
This paper evaluates the efficiency of the extended version of the KDamper (EKD) as a seismic retrofitting solution for existing multi-story building structures. Two distinct approaches are investigated. The first one considers the implementation of an EKD device at the structure’s base level, a straightforward approach that simplifies the design process. The second one involves the dispersion of multiple EKDs throughout the height of the structure, a more computationally demanding approach, that aims to control higher modes, especially in high-rise structures. Three test cases are investigated, representing low, mid, and high-rise building structures. The primary objective is to provide insights into the effectiveness of each retrofitting strategy based on the structure’s height and number of stories, presenting a comprehensive assessment of the advantages and disadvantages of each option. Overall, the results underscore the positive influence of the EKD system on the dynamic response of all examined multi-story structures, establishing it as a compelling technology for seismic retrofitting. Designers can compare different retrofitting strategies based on building height and number of stories to choose the most efficient option.